Implementasi Sistem Pembayaran Digital QRIS dalam Meningkatkan Pelayanan Publik (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Along with the rapid growth of digital media, various forms of digital transactions have also developed.1 This development has driven changes in the payment system in Indonesia, one of which is through the implementation of QRIS (Quick Response Code Indonesian Standard). Despite its increasingly widespread use, there are still few studies that systematically examine user perceptions and the effectiveness of QRIS in improving transaction efficiency and strengthening the digital financial system. The purpose of this study is to identify and comprehensively analyze the results of previous studies related to QRIS use through a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar and Garuda using the keywords